2019
DOI: 10.3390/ma12203373
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Silver Nanoparticles Fixed on TiO2 Nanotubes as Simple and Efficient Substrates for Surface Enhanced Raman Scattering

Abstract: In this work we show that ordered freestanding titanium oxide nanotubes (TiO2 NT) may be used as substrates for the simple and efficient immobilization of anisotropic plasmonic nanoparticles. This is important because anisotropic plasmonic nanostructures usually give greater spectral enhancement than spherical nanoparticles. The size of the pores in a layer of titanium oxide nanotubes can be easily fitted to the size of many silver plasmonic nanoparticles highly active in SERS (surface-enhanced Raman scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…The peak at 531 eV illustrated in Figure 3 b can be assigned as the lattice oxygen of synthesized Ag-doped ZnO NSs and presents O 2− ionization [ 33 ]. Besides, Ag3d XPS is doubled at 366.8 and 373.0 eV with respect to Ag3d 5/2 and Ag3d 3/2 , with a separation of 6.2 eV, as demonstrated in Figure 3 c, provides the evidence of existence Ag + species [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 531 eV illustrated in Figure 3 b can be assigned as the lattice oxygen of synthesized Ag-doped ZnO NSs and presents O 2− ionization [ 33 ]. Besides, Ag3d XPS is doubled at 366.8 and 373.0 eV with respect to Ag3d 5/2 and Ag3d 3/2 , with a separation of 6.2 eV, as demonstrated in Figure 3 c, provides the evidence of existence Ag + species [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was demonstrated that by having a similar amount of metal deposit, the structure of the TiO 2 surface will play a key role in the SERS activity [20]. As a result, TiO 2 NTs are promising supports because, by controlling the geometry upon conditioning anodization parameters, it is possible to have metallic nanoparticles deposited in the gaps between each tube to provide a large number of hot spots as well as a homogeneous surface coverage [11,75].…”
Section: Titanium Dioxide Nanotubes (Tio 2 Nts) Prepared By Anodizationmentioning
confidence: 99%
“…It is also possible to attach previously synthesized plasmonic nanoparticles to TiO 2 nanotubes [ 24 , 25 ]. In such a case, one can attach a large number of very similar (having practically the same shape and size) plasmonic nanoparticles to the TiO 2 nanotubes.…”
Section: Non-metallic Nanostructured Thin Films Covered By Plasmonmentioning
confidence: 99%
“…Ambroziak et al found that the SERS enhancement generated by the SERS substrate produced by the attachment of cubic silver nanoparticles to TiO 2 nanotubes (when only a part of the outside surface is covered by the plasmonic material) is even higher than the SERS enhancement generated by the standard electrochemically nanostructured solid silver substrate. Moreover, the spatial reproducibility of the SERS enhancement factor for such composite TiO 2 -nanotubes/cubic-Ag nanoparticles substrate is larger than that for the standard electrochemically nanostructured silver substrate [ 24 ].…”
Section: Non-metallic Nanostructured Thin Films Covered By Plasmonmentioning
confidence: 99%